Large-scale phylogenetic analysis for the study of zoonosis and assessment of influenza surveillance - Janies, Daniel A. (2007)
We performed a phylogenetic analysis of 2359 hemagglutinin sequences of influenza A. We find multiple host shifts of all polarities among swine, humans, and birds. We also describe novel methods to assess the quality of surveillance and apply these methods to the public sequence record.